A well-fabricated Ru@C material derived from Ru/Zn-MOF with high activity and stability in the hydrogenation of 4-chloronitrobenzene. Issue 12 (8th March 2023) - Wang, Zijian; Zhang, Jiaxin; Yan, Lele; Zhao, Bo; Zheng, Lin; Guo, Haoran; Yue, Yuxue; Han, Deman; Chen, Xianlang; Li, Rongrong
Abstract : Selective hydrogenation of 4-chloronitrobenzene (4-CNB) over catalysts having suitable Ru vacancies with excellent conversion, selectivity and stability is presented. Abstract : 4-Chloroaniline (4-CAN) plays an important role in chemical and industrial production. However, it remains a challenge to avoid the hydrogenation of the C–Cl bond in the synthesis process to improve selectivity under high activity conditions. In this study, we in situ fabricated ruthenium nanoparticles (Ru NPs) containing vacancies inserted into porous carbon (Ru@C-2) as a highly efficient catalyst for the catalytic hydrogenation of 4-chloronitrobenzene (4-CNB) with remarkable conversion (99.9%), selectivity (99.9%), and stability. Experiments and theoretical calculations indicate that the appropriate Ru vacancies affect the charge distribution of the Ru@C-2 catalyst, promote the electron transfer between the Ru metal and support, and increase the active sites of the Ru metal, thus facilitating the adsorption of 4-CNB and the desorption of 4-CAN to improve the activity and stability of the catalyst. This study can provide some enlightenment for the development of new 4-CNB hydrogenation catalysts.